Fostering Improvements in Equitable Care Delivery: Insights From the Health Equity Report Card (HERC) Pilot in Academic Cancer Centers - Ashley Orr; Taneal D. Carter; Mallory Stubblebine; Heather McKee Hurwitz; Tiffany Go; Leticia Mercado; Darryl Outlaw; Elizabeth Bouchard; Levent Dumenci; Crystal S. Denlinger; Alyssa A. Schatz (Journal of the National Comprehensive Cancer Network, 2026)
Background: The Health Equity Report Card (HERC) was developed to support institutions in measuring equitable care practices and implementing improvement efforts. An objective of this study was to determine whether academic cancer centers can use their baseline HERC scores to identify institution-specific strategies to improve equitable care delivery. Methods: This quality improvement study collected quantitative and qualitative data from 5 NCCN Member Institutions about their quality improvement efforts in response to their HERC baseline scores. This project took place over 18 months, between April 2022 and October 2024. Results: The secondary objective of utilizing HERC baseline scores to identify improvement efforts was met, with 4 sites identifying and implementing improvement efforts in at least one domain. Sites reported barriers and facilitators for their improvement projects. Utilization of the HERC to develop strategies to improve equitable care delivery in response to baseline scores was feasible in academic cancer centers. Four sites used the HERC findings to support and prioritize strategies that had been previously identified and discussed but not fully implemented. Two sites identified new improvement efforts that had not been previously considered by their institution. The complexity of the health system, collaboration across departments, resource allocation, competing priorities, and leadership support were discussed as both challenges and facilitators in identifying and implementing improvement strategies. Conclusions: The HERC may offer a useful framework for prioritizing and assessing improvement efforts for academic cancer centers seeking to improve equitable care delivery.